Prasasti Batu Jimbar di Dusun Bet Ngandang Desa Intaran: Kajian Epigrafi - Kurnia Saraswati, Ni Putu; Saptajaya, Ida Bagus (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p29, 2018)
The purposed this study is to know linguistic aspects of the Batu Jimbar inscription which includes script, language, spelling, and affixation. Furthermore, the research also discussed about the social aspects contained. Data collection methods used in this study were observation, literature study, and interviews with data processing through qualitative, interpretative, and epigrafi analysis. Based on the analysis of Batu Jimbar inscription, it can be known that the inscription used the ancient Balinese letters with the Old Javanese language. Batu Jimbar inscription used spellings that had been developed in the previous era, such as prefixes para-, ma-, pa-, ka-, sa-, um-, a-, and ha-, suffixes –?n, -nya, -an, and confixes (pa- + -ma), (ma- + -an), (a- + -an), (ka- + -an), ( ka- + -nya), (maka + -an). Socio-cultural aspects contained in the Batu Jimbar inscription is about the rights and obligations and social organizations that exist in it such as the rights and obligations that must be implemented by Indrapura residents by worshiping Bhatara (Gods) at Bukit Unggal (Hill).